Oxidation and dissolution of refractory gold concentrate in alkaline hypochlorite solutions - Regidor, Hanna Czarise E.; Mendoza, Herman D.; Manalo, Mena G. (2022)
Access online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/8903/7829
Keywords: Electrochemical analysis; Oxidation; Gold ores